Status and future of the soft X-ray free-electron laser beamline at the SHINE - Liu, Tao; Huang, Nanshun; Yang, Hanxiang; Qi, Zheng; Zhang, Kaiqing; Gao, Zhangfeng; Chen, Si; Feng, Chao; Zhang, Wei; Luo, Hang; Fu, Xiaoxi; Liu, He; et al. (Frontiers in Physics, 2023)
The SHINE, a high repetition-rate X-ray FEL facility, is under construction in Shanghai which aims at generating X-rays between 0.4 and 25 keV with three FEL lines at repetition rate up to 1MHz. The soft X-ray FEL line, FEL-II will be ready for commissioning in 2025 firstly. It is designed to cover the photon energy from 0.4 to 3 keV, in which the baselines of the FEL operation modes are SASE, self-seeding, EEHG and polarization control. Therefore, high repetition-rate external seed laser, large period length modulator, soft X-ray monochromator, planar undulator and elliptically polarized undulator have been adopted in the FEL-II line. Several potentials such as ultra-short pulse mode and multi-color mode are also foreseeable without significant equipment changes in the follow-up operation. Besides, the double period undulator design is suggested for the EEHG commissioning, and meanwhile it is great potential to break through the unreachable energy of the fully coherent X-ray in the future. It is looking forward to deliver SASE radiation and fully coherent radiation in all the wavelengths of interest.